Kajian Awal : Respon Eksplan Nodus terhadap Inisiasi Tunas Mikro Tanaman Karet (Hevea brasiliensis Muell. Arg.) pada Media dan Genotipe Berbeda - Heri Hidayat; Luthfi Aziz M. Siregar; Eva Sartini Bayu (Jurnal Agroekoteknologi, 2015)
The aim of the research was to determine the proper medium for micro shoot induction of rubber plant from the nodes explants of diffrent genotypes. The research was conducted at the rubber plant Micocutting Laboratory PT. Perkebunan Nusantara III Kebun Gunung Pamela, Tebing Tinggi, North Sumatera, Indonesia. The research began from September to December 2014. the completely randomized design was used with twenty four treathments and five replications. The result showed that the genotype and diffrent composition medium gave significantly diffrent on percent of explant forming shoot. Meanwhile, for parameter life explant the genotype and diffrent composition medium no significantly diffrent.Keywords: rubber, micro shoot, genotype, in vitro medium